Relationship Marketing in High Technology Based SMEs: A Customer Perspective - Louisa Huxtable-Thomas (Let’s Get Engaged! Crossing the Threshold of Marketing’s Engagement Era, 2016)
This chapter builds upon work by Parry et al (2011) to develop an understanding of marketing and customer relationships in software SMEs. Based on primary research undertaken in Wales (UK),